Sociodemographic and Behavioral Determinants of Smoking : A Secondary Analysis in the 2023 Indonesia Health Survei (SKI) - Edi Junaidi; Muhammad Iqbal; Cut Syarifa Thursina; Rachmi Nurkhalika; Helza Oktaria; Yeti Raheli (An Idea Health Journal, 2026)
Background: Smoking constitutes a major risk factor for non-communicable diseases and remains a significant public health issue in Indonesia. This study analyzes determinants of smoking status based on sociodemographic and behavioral characteristics from the 2023 Indonesian Health Survey (SKI). Methods: This study employed a cross-sectional design utilizing secondary data from the 2023 Indonesian Health Survei. A total sampling technique was applied, initially including 877,531 respondents. After excluding individuals with missing data or those who did not respond to the cigarette variable (166,246), the final sample comprised 711,285 participants. Bivariate analyses and multivariate logistic regression identified dominant factors associated with smoking status. Result: Smoking prevalence was 25.49% (181,278), while non-smoking was 74.51% (530,007). Multivariate analysis showed gender as the strongest predictor, with men having much higher odds of smoking than women (OR = 96.95; p < 0.001). Other significant factors were rural residence (OR = 1.133; p < 0.001), marital status (OR = 0.676; p < 0.001), low education (OR = 0.463; p < 0.001), employment status (OR = 1.133; p < 0.001), non-BPJS health insurance (OR = 0.884; p < 0.001), occasional exposure to other smokers (OR = 4.130; p < 0.001), and alcohol use (OR = 3.314; p < 0.001). The model showed strong explanatory power (Pseudo R² = 0.485). Conclusion: Tobacco control strategies should be integrated with screening and counseling for risky behaviors, including alcohol consumption. Additionally, smoking cessation services should be adapted and expanded to address both rural and urban contexts.